Additive Utility Functions and Linear Engel Curves - Pollak, Robert A. (Review of Economic Studies, 1971)
Journal Article Additive Utility Functions and Linear Engel Curves Get access Robert A. Pollak Robert A. Pollak University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 4, October 1971, Pages 401–414, https://doi.org/10.2307/2296686 Published: 01 October 1971